The predictive value of trunk/leg fat ratio for type 2 diabetes mellitus remission after bariatric surgery: A new observation and insight - Cui, Beibei; Li, Weizheng; Wang, Guohui; Li, Pengzhou; Zhu, Liyong; Zhu, Shaihong (Frontiers in Endocrinology, 2022)
Background Emerging evidence supported the significant role of body composition and fat distribution in the etiology and pathogenesis of Type 2 diabetes mellitus (T2DM). Objective To assess the predictive value of representative parameters of body composition and fat distribution for T2DM remission after bariatric surgery. Methods A total of 72 patients with T2DM who underwent bariatric surgery in our center between September 2010 and December 2018 were included in this retrospective observational study. Diabetes remission was defined according to the American Diabetes Association criteria released in 2021. Body fat percentage, skeletal muscle index, Android/Gynoid ratio and trunk/leg fat ratio were derived from dual-energy X-ray absorptiometry and assessed. Results A total of 40 patients (56%) achieved remission among 72 patients. Patients in the remission group had higher body fat percentage and lower trunk/leg fat ratio than those in the non-remission group. The area under the receiver operating characteristic curve (AUC) for predicting T2DM remission was higher for trunk/leg fat ratio (0.784), compared to BMI (AUC 0. 0.690) and body fat percentage (AUC 0.688). The prediction model (AUC 0.883) including age, duration of T2DM, and trunk/leg fat ratio performed better than the ABCD score (AUC 0.809) and the DiaRem score (AUC 0.792). A nonlinear relationship was observed between trunk/leg fat ratio and BMI. Conclusion Trunk/leg fat ratio is a promising predictor for T2DM remission after bariatric surgery.